Streamlining Regional Regulations with Omnibus Law for Legal Harmonization: Penyederhanaan Peraturan Daerah dengan Omnibus Law untuk Harmonisasi Hukum - Purwanto, Purwanto; Sulaksono, Sulaksono; Tamsil, Tamsil; Prasetio, Dicky Eko (Rechtsidee, 2024)
Background: Regional regulations (Perda) in Indonesia often face issues of overlap and inefficiency. Specific Background: The Omnibus Law method, known for simplifying and harmonizing regulations, has been applied nationally but remains underexplored locally. Knowledge Gap: Its practical application at the regional level, including challenges and opportunities, lacks sufficient research. Aims: This study examines the legal reconstruction of Perda using the Omnibus Law to improve regulatory efficiency and alignment with national laws. Results: The method streamlines regulations, enhances coherence, and boosts legal certainty but faces challenges such as stakeholder resistance and capacity limitations. Novelty: The research highlights the method's transformative potential for resolving Indonesia's regulatory complexities. Implications: It advocates for capacity-building, participatory processes, and effective oversight to achieve cohesive and responsive governance. Highlights: Regulatory Simplification: The Omnibus Law integrates overlapping regional laws into a single, cohesive framework. Challenges: Stakeholder resistance and limited local capacity hinder effective implementation. Opportunities: Enhances legal certainty and fosters better alignment with national regulations. Keywords: Omnibus Law, Regional Regulations, Legal Reconstruction, Regulatory Efficiency, Governance Harmonization